Modern views on medical provision of patients with rare diseases of the circulatory system in Ukraine and the world - I. S. Datsenko; A. V. Kabachna; V. S. Hulpa (The State Expert Center of the Ministry of Health of Ukraine, 2021)
There are more than 300 million people in the world, including up to 30 million Europeans and 25 million North Americans, who suffer from one or more rare (orphan) diseases. According to the Union of Orphan Diseases of Ukraine, there are at least 1.5-2 million patients suffering from rare diseases (RD). There is a global trend of increasing the number of patients suffering from RD, which indicates the relevance of research on improving the mechanisms for providing them with medical, pharmaceutical and social care. The objective of the paper was the analysis of modern components of the process of organizing medical support for patients suffering from rare diseases in Ukraine and foreign countries and determining scientific and methodological approaches to improving the pharmaceutical support of this category of patients on the example of patients suffering from rare diseases of the circulatory system in Ukraine. The object of the study was information obtained in the relevant regulatory legal acts in force in the territory of Ukraine and information materials on the organization of medical care for patients suffering from rare diseases in foreign countries. System-based survey, documentary, and graphic research methods were used. According to the results of the analysis of regulatory documents and information materials on the organization of medical care for patients suffering from RD in other foreign countries, despite the existing standard regulation of medical support for patients suffering from RD in Ukraine, the state does not fully fulfill the obligations necessary for this category of patients. There is no State Register of Patients suffering from RD in Ukraine, as well as Special Reference Centers for Organizing Medical Support for Patients, which hinders proper provision of them with drugs, and also affects their quality of life. To objectively determine the real expenditures of budgets for funding all components of the process of medical care for orphan patients, it is necessary to use its main provisions to determine the strategy of medical care for patients suffering from orphan diseases. High-cost, imported antithrombotic agents, diuretics, and calcium antagonists are used in the pharmacotherapy of patients suffering from rare diseases of the circulatory system. There is a need to review and create a pharmaceutical component of Unified clinical protocols for the treatment of most nosologies of this group of diseases in the context of pharmacoeconomic studies to establish the clinical efficiency and economic feasibility of the introduced drugs.